LA DIGNIDAD DEL CONDENADO A PENA DE PRISIÓN EN EL DERECHO PENAL Y PENITENCIARIO COLOMBIANO (2016)
The following is an essay on the development of the execution of criminal sanctions in Colombia over the past two decades , which gives a glimpse into the dignity of doomed from the declaration of unconstitutionality in prisons by the H. Court constitutional says the development of public policies criminals conducted by the state and identified as a problem and legal uncertainty created by the lack of a closing to make interpretations of the law on enforcement of criminal sanctions to generate greater legal certainty and homogeneity of decisions in different judicial districts.